SPECTROPHOTOMETER FOR RESEARCH OF THE ATMOSPHERIC OZONE - POSITIONING OF THE EXECUTIVE OPERATING PARTS - Chervenkov, Dimitar; Chernokozhev, Plamen (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper is about spectrophotometer for research ofthe atmospheric ozone and more specifically about a method for positioning of executive operating parts withi electromechanical feedback. Of special interest is the high positioning precision, independently of the rotation direction when using a classic elemental basis, repair suitability and easy operation. A principle is implemented for the precise positioning of the executive operating organs with an electromechanical feed-back. Its work is highly reliable. The implementation is possible with simple parts and is electrically adaptable with a microprocessor system and the leading motor. Various applicable schemes can be created with different precision of work which depends on the preliminary relation in the mechanic transmission. Depending on the wearing out with time, the principle allows it to be read by the microprocessor system in order to keep the necessary precision. A system with such feed-back can work with one- and twodirection circular motion.